The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/v13030477
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Ahp2, a Lytic Bacteriophage of Aeromonas hydrophila

Abstract: Aeromonas hydrophila is an opportunistic pathogen that infects fish, amphibians, mammals, and humans. This study isolated a myophage, vB_AhyM_Ahp2 (Ahp2), that lytically infects A. hydrophila. We observed that 96% of the Ahp2 particles adsorbed to A. hydrophila within 18 min. Ahp2 also showed a latent period of 15 min with a burst size of 142 PFU/cell. This phage has a linear double-stranded DNA genome of 47,331 bp with a GC content of 57%. At least 20 Ahp2 proteins were detected by SDS-polyacrylamide gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…In general, phages are highly specific, infecting only one bacterial genus or even particular strains [ 224 ]. Most Aeromonas phages showed narrow host specificity, infecting only the original host bacterium [ 51 , 93 , 150 , 214 ] or strains of a given bacterial species [ 91 , 94 , 95 , 149 , 209 , 220 , 230 , 231 ] ( Table S2 ). The majority of marine phages are highly host-specific [ 232 , 233 , 234 ], and about 73% lyse only the original host bacterium [ 234 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, phages are highly specific, infecting only one bacterial genus or even particular strains [ 224 ]. Most Aeromonas phages showed narrow host specificity, infecting only the original host bacterium [ 51 , 93 , 150 , 214 ] or strains of a given bacterial species [ 91 , 94 , 95 , 149 , 209 , 220 , 230 , 231 ] ( Table S2 ). The majority of marine phages are highly host-specific [ 232 , 233 , 234 ], and about 73% lyse only the original host bacterium [ 234 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
“…In other studies, A. hydrophila phage adsorption reached over 90% after 40 min [ 95 ], while El- Araby et al (2016) showed a 51% and 66.8% adsorption after 20 and 30 min, respectively [ 93 ]. Phage Ahp2 showed a high adsorption efficacy with 96% of phage particles being adsorbed to A. hydrophila in the first 18 min [ 230 ]. Chen et al (2018) reported that the five isolated phages (AS-szw, AS-yj, AS-zj, AS-sw and AS-gz) showed strong adsorption to A. salmonicida surface and approximately 90% (2.7 × 10 4 PFU/mL out of 3.1 × 10 4 PFU/mL) of phage particles adsorbed to A. salmonicida within the first 5 min [ 217 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
“…100 μl of supernatant was removed to calculate the titer of unadsorbed phages. One-step growth and burst-size measurements were performed as previously reported 58 . All experiments were performed at least twice in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…The host range was determined by spotting 5 µl of phage lysate on the lawns of investigated cultures on TSB3S agar plates, as previously described 58 . A clear spot indicates host sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Aeromonas myophage genomics and biology have been described previously in comprehensive reviews [17,20]. Recently, a number of new Aeromonas phages with podovirus morphotype were described and their genomes appeared in the NCBI GenBank database [19,38,40,[42][43][44]. To evaluate the relations between the studied AerP_220 phage and other Aeromonas phages, vConTACT2 analysis was performed for all Aeromonas phage genomes available in the GenBank database (Table S2, Figure 6).…”
Section: Protein-based Similarity Networkmentioning
confidence: 99%